Impact of radial deviation of electron beam on backward wave oscillation in helix TWT. Issue 14 (13th June 2018) - Zhang, Jin; Yuan, Huiyu; Zhao, Xingqun; Bai, Ningfeng; Shen, Changsheng; Fan, Hehong; Sun, Xiaohan; Chen, Bo; Feng, Jinjun; Yan, Tiechang
Abstract : In this study, the impact of radial deviation of the electron beam on backward wave oscillation (BWO) in a helix travelling wave tube (TWT) is explored. By using CST simulation, the output power of a helix TWT with the electron beam deviation of 0.01 mm is obtained and compared with that of a normal TWT. We found that the output power of the helix TWT changes by 40 W. By analysing the backward wave signal when the TWT works at 11 GHz for different values of the radial deviation of the electron beam, we found that the backward wave amplitude increases as the radial deviation of the electron beam increases. When the radial deviation reaches 0.04 mm (9.5% relative to the electron beam), the backward wave starts to oscillate. When the radial deviation reaches 0.06 mm (14.3% relative to the electron beam), the BWO becomes more severe. It has been proved that the radial deviation of the electron beam is one of the contributing factors for BWO in the helix TWT.